Concept Of Terms In Understanding Absolute Water Law Contemporary Legal Study Modern Fiqh Perspective - Abd Razak (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The interpretation of the concept of istihalah in the context of modern technology, such as wastewater treatment and recycling, triggers new problems. Although the concept of istihalah has been accepted in classical fiqh, its application in the contemporary world raises challenges related to the scientific validity and practice of water treatment that changes the nature of water. This research uses a library research method , which focuses on the study of literature and written documents relevant to the research topic. The main data sources in this research are scientific journal articles and published research reports. The research results show that: 1). The form of the concept of istihalah in understanding the law of absolute water is that istihalah is the change of an impure substance into a new substance that is totally holy and in absolute water fiqh, this means that unclean water that has completely changed its nature can again be considered holy and purifying. 2). The application of the concept of istihalah in understanding absolute water law in contemporary legal studies is that in the modern context, istihalah is used to authorize the use of recycled water, as long as the purification process removes all unclean properties and meets purity standards. 3). The Ulama's view of the concept of istihalah in understanding absolute water law in contemporary legal studies is that contemporary Ulama generally accept the concept of istihalah as the basis for the ability to use recycled water for purification, provided that the change in the substance is complete and scientifically proven.